Innovation Barriers across Firms and Countries - Werner Hölzl; Jürgen Janger (Austrian Institute of Economic Research (WIFO), 2012)
This paper studies differences in the perception of innovation barriers between innovative and non-innovative firms for 18 EU countries. The countries are grouped by their distance to the technological frontier using Community Innovation Surveys for the years 2002-2004 and 2004-2006. The results show that non-innovators interested in innovation are much more likely to perceive barriers than non-innovators that are not interested in innovation activities. With regard to differences between country groups there is a clear indication that innovation barriers related to the availability of skilled labour, innovation partners and knowledge are more important for firms located in countries close to the frontier, while the opposite is true regarding the availability of external finance. Although the share of innovators decreases with the distance to the technological frontier, the share of barrier-related innovators increases. The results demonstrate the usefulness of the innovation barrier approach to understand the determinants of innovative activity at the firm level and to priority-setting within innovation policies.
Keywords: 330; Innovation barriers; Europe; innovation policy; Industrieforschung; Institutionelle Infrastruktur; Technische Effizienz; Technologiepolitik; EU-Staaten